Herrero, Fabián, El fraile Castañeda, ¿El “trompeta de la discordia” ?, Buenos Aires, Prometeo, 2020, pp. 409. - Eiris, Ariel Alberto (2021)
Fil: Eiris, Ariel Alberto. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina